LE VERDISSEMENT DE LA PRESSE. LA NÉOLOGIE TERMINOLOGIQUE ENTRE MÉTAPHORE ET MANIPULATION - GAGLIANO, Chiara (Studia Universitatis Babeș-Bolyai Philologia, 2024)
The Greening of the Press. Terminological Neology between Metaphor and Manipulation. Through the analysis of Cop26 eco-political discourses, collected from the newspapers Le Monde, Libération, Le Devoir and La Presse, the aim of the contribution is to propose a systematisation of ecological green. Rooted in political terminology while used in a diplomatic and mediatic context, the colour provokes a counter-discourse that calls into question accusations of greenwashing. The referential domain linked to green is largely that of the energy crisis on the one hand, and the opportunities of a sustainable approach to global economy on the other, themes analysed as semantic preferences of the lexeme, as well as discursive contexts that evoke promise/hope or deception/catastrophe. The synchronic perspective is chosen to probe the topicality of environmental lexis in journalistic contexts, whose stylistic and creative turns of phrase also contribute to enriching the specialised terminology, and to shape the double perception of the colour in the collective discursive memory. Ecologizarea presei. Neologie terminologică între metaforă și manipulare. Prin analiza discursurilor eco-politice din Cop26, colectate din ziarele Le Monde, Libération, Le Devoir și La Presse, scopul acestei contribuții este de a propune o sistematizare a termenului/culorii verzi Înrădăcinată în terminologia politică, deși utilizată într-un context diplomatic și mediatic, culoarea provoacă un contra-discurs care pune sub semnul întrebării acuzațiile de greenwashing. Domeniul referențial legat de verde este în mare măsură cel al crizei energetice, pe de o parte, și al oportunităților unei abordări durabile a economiei globale, pe de altă parte, teme analizate ca preferințe semantice ale lexemului, precum și contexte discursive care evocă promisiuni/ speranțe sau înșelăciune/catastrofă. Este aleasă perspectiva sincronică pentru a examina, în contexte jurnalistice, vocabularul actual specific domeniului mediului înconjurător, vocabular a cărui frazeologie expresivă și creativă contribuie, de asemenea, la îmbogățirea terminologiei de specialitate și la conturarea dublei percepții a culorii în memoria discursivă colectivă. Cuvinte-cheie: neologie, tehnolect în domeniul ecologiei, discurs jurnalistic, anglicisme Article history: Received 10 October 2023; Revised 15 December 2023; Accepted 31 January 2024; Available online 27 March 2024; Available print 27 March 2024